PREPARATION OF FUTURE PRIMARY SCHOOL TEACHERS FOR INTELLECTUAL ACTIVITIES ON THE BASIS OF INTELLECTUAL SYSTEMS OF KNOWLEDGE ACQUISITION - Pardabayeva Dilshoda; Gafforova Zarnigor (Web of Journals Publishing, 2024)
This article provides information on the preparation of primary school teachers for intellectual activity, as well as the work that needs to be done in this regard.
Keywords: Intellectual activity, foreign experience, quality assessment of education, teacher, student.